Effect of Various Doses of Cassava on Growth and Production of Mung Beans (Vigna Radiata L) - Latif Prasetio; Arman Effendi AR; Erlida Ariani; Sukemi Indra Saputra (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
The horticultural sector is growing and the need for its products is also increasing, including the need for green beans, but its availability is limited by land conditions that are poor in organic matter, so it needs to be treated with the addition of organic fertilizers such as vermicompost. This study aims to determine the effect of vermicompost and obtain the best dose for the growth and production of mung bean (Vigna radiata L.). The study was conducted using a factorial Completely Randomized Design (CRD) consisting of a single factor, namely the provision of vermicompost. From these factors, there were four levels of treatment (0, 5, 15, and 25 tons ha-1) and each treatment was given three replications so that there were 12 experimental units. The parameters reviewed were plant height, total productive branches, flower age, harvest age, total pods planted, percentage of pithy pods, weight of planted seeds, weight of seeds per plot, and weight of 100 seeds. The dose of vermicompost 25 ton.ha-1 was better than the dose of 0 ton.ha-1, the dose of 5 ton.ha-1, and the dose of 15 tons/ha. The treatment can increase plant height, total productive branches, total pods planted, percentage of pithy pods, weight of seeds planted, weight of seeds per plot, and weight of 100 seeds.